2021
DOI: 10.1093/cid/ciab962
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Early Treatment With Favipiravir on Disease Progression Among High-Risk Patients With Coronavirus Disease 2019 (COVID-19): A Randomized, Open-Label Clinical Trial

Abstract: Background Role of favipiravir in preventing disease progression in COVID-19 remains uncertain. We aimed to determine its effect in preventing disease progression from non-hypoxia to hypoxia among high risk COVID-19 patients. Study design This was an open-label, randomized clinical trial conducted at 14 public hospitals across Malaysia from February to June 2021 among 500 symptomatic, RT-PCR confirmed COVID-19 patients, aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Some small, open-label studies have indicated benefits in terms of clinical outcomes [25][26][27][28] or viral shedding [13,26]. However, other studies have indicated no clinically important benefit [29,30], including when given in early disease [31]. These studies were open label with heterogenous populations often including hospitalised patients, where antiviral treatment is expected to be less effective.…”
Section: By Including a Placebo-controlled Lopinavir-ritonavir Monoth...mentioning
confidence: 99%
“…Some small, open-label studies have indicated benefits in terms of clinical outcomes [25][26][27][28] or viral shedding [13,26]. However, other studies have indicated no clinically important benefit [29,30], including when given in early disease [31]. These studies were open label with heterogenous populations often including hospitalised patients, where antiviral treatment is expected to be less effective.…”
Section: By Including a Placebo-controlled Lopinavir-ritonavir Monoth...mentioning
confidence: 99%
“…Our systematic literature search retrieved 1493 hits, of which 613 were unique. After screening, we included six randomized controlled trials ( Table 1 ) [1] , [2] , [3] , [4] , [5] , [6] , with a total of 1,669 patients with COVID-19. The meta-analysis of the included trials [1] , [2] , [3] , [4] , [5] , [6] revealed no significant difference in the odds of mortality with the use of favipiravir among patients with COVID-19, relative to non-use of favipiravir; the estimated effect though indicated increased mortality ( Figure 1 ; pooled odds ratio = 1.09; 95% confidence interval 0.76 to 1.56) but is without adequate evidence against the null hypothesis of ‘no significant difference,’ at the current sample size.…”
Section: Introductionmentioning
confidence: 99%
“…The meta-analysis of the included trials [1] , [2] , [3] , [4] , [5] , [6] revealed no significant difference in the odds of mortality with the use of favipiravir among patients with COVID-19, relative to non-use of favipiravir; the estimated effect though indicated increased mortality ( Figure 1 ; pooled odds ratio = 1.09; 95% confidence interval 0.76 to 1.56) but is without adequate evidence against the null hypothesis of ‘no significant difference,’ at the current sample size.…”
Section: Introductionmentioning
confidence: 99%
“…A dose regiment of 1600 mg twice daily on day 1, followed by 600 mg twice daily for 4 days was recommended [ 5 , 6 ]. As subsequent clinical researches demonstrated that favipiravir was not superior to standard supportive care in terms of reducing COVID-19 related hospitalization rates or mortality, favipiravir was dropped from the COVID-19 Guideline for Management of Adult Patients on revision dated 20 December 2021 [ 7 – 9 ]. It was also noted that the drug could be used when the treating physician deems necessary, as some of the clinical researches reported reduced duration of symptoms [ 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%